The Aggression Features of the Soldiers According to their Rank Status - Vasiliev, G. V. (Psychological Prospects Journal, 2012)
The military aggression features as a function of status rank are analyzed. It was established that the conscripts compared with a group of mercenaries and warrants tend to exercise more physical aggression, the total value оf their aggressiveness and decision is higher. Contract servicemen, alongside with a high enough level of physical aggression, also have higher indicators of suspicion and index of agressiveness, and the highest comparing with the other groups hostility index and level of aggression. The group of warrant officers as compared with the other groups has more severe forms of aggression such as indirect aggression, irritability, resentment, suspicion and guilt. This category of personnel is also characterized by higher rates of aggression and hostility, aggressiveness level and the total value of aggressiveness and decision.